Measurement of radioactive contamination in the high-resistivity silicon CCDs of the DAMIC experiment - Aguilar Arevalo, A. (2015)
We present measurements of radioactive contamination in the high-resistivity silicon charge-coupled devices (CCDs) used by the DAMIC experiment to search for dark matter particles. Novel analysis methods, which exploit the unique spatial resolution of CCDs, were developed to identify α and β particles. Uranium and thorium contamination in the CCD bulk was measured through α spectroscopy, with an upper limit on the 238 U ( 232 Th) decay rate of 5 (15) kg −1 d −1 at 95% CL. We also searched for pairs of spatially correlated electron tracks separated in time by up to tens of days, as expected from 32 Si ? 32 P or 210 Pb ? 210 Bi sequences of β decays. The decay −1 d −1 (95% CI). An upper limit of ∼35 kg −1 d −1 (95% CL) rate of 32 Si was found to be 80 +110 −65 kg on the 210 Pb decay rate was obtained independently by α spectroscopy and the β decay sequence search. These levels of radioactive contamination are sufficiently low for the successful operation of CCDs in the forthcoming 100 g DAMIC detector.